1985
DOI: 10.1007/bf02481119
|View full text |Cite
|
Sign up to set email alerts
|

Maximum likelihood prediction

Abstract: SummaryThe principle of maximum likelihood is applied to the joint prediction and estimation of a future random variable and an unknown parameter. We assume dependence between present and future, and the approach is non-Bayesian. Our principal application is to the prediction of higher order statistics from lower ones in Type II censored random samples. Some simple criteria for existence and uniqueness of the predictor are given for this situation and the methods are illustrated with several examples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(28 citation statements)
references
References 10 publications
0
28
0
Order By: Relevance
“…In the literature, one frequently used predictor is M LP which has been discussed by Kaminsky and Rhodin (1985) for ordinary Type-II right censored samples. CM P is another possible predictor.…”
Section: Is Unbiased Predictor If the Prediction Error T − Y J:r I Hamentioning
confidence: 99%
“…In the literature, one frequently used predictor is M LP which has been discussed by Kaminsky and Rhodin (1985) for ordinary Type-II right censored samples. CM P is another possible predictor.…”
Section: Is Unbiased Predictor If the Prediction Error T − Y J:r I Hamentioning
confidence: 99%
“…The likelihood approach was suggested by Kaminsky and Rhodin (1985) for predicting future observations. See also Raqab and Nagaraja (1995) and Raqab et al (2010).…”
Section: Maximum Likelihood Reconstructormentioning
confidence: 99%
“…Several authors have considered prediction intervals for future order statistics based on observed order statistics in parametric and nonparametric settings. See for example, Lawless (1977), Nagaraja (1984), Kaminsky and Rhodin (1985), Chou (1988), Nagaraja (1995), Raqab and Nagaraja (1995), Hsieh (1997), Kaminsky and Nelson (1998) and Abdel-Aty et al (2007) and so on.…”
Section: Introductionmentioning
confidence: 97%